Interaction studies of Serendipita indica and Zhihengliuella sp. ISTPL4 and their synergistic role in growth promotion in rice - Sharma, Neha; Dabral, Surbhi; Tyagi, Jaagriti; Yadav, Gaurav; Aggarwal, Himanshi; Joshi, Naveen Chandra; Varma, Ajit; Koul, Monika; Choudhary, Devendra Kumar; Mishra, Arti (Frontiers in Plant Science, 2023)
Rapid urbanization and globalization demand increasing agricultural productivity. Soil nutrient supply capacity is continuously decreasing due to soil erosion, degradation, salt deposition, undesired element, metal deposition, water scarcity, and an uneven nutrient delivery system. Rice cultivation requires a large amount of water which is becoming detrimental due to these activities. There is a need to increase its productivity. Microbial inoculants are becoming increasingly important in achieving sustainable agricultural production systems. The current study was conducted to investigate the interaction between the root endophytic fungus Serendipita indica (S. indica) and the actinobacterium Zhihengliuella sp. ISTPL4 (Z. sp. ISTPL4) and their synergistic effects on the growth of rice (Oryza sativa L). Both S. indica and Z. sp. ISTPL4 showed positive interactions. Growth of S. indica was observed at different days after Z. sp. ISTPL4 inoculation, and stimulated growth of S. indica was observed when Z. sp. ISTPL4 was inoculated at 5 dafi (days after fungal inoculation). Z. sp. ISTPL4 promoted the growth of S. indica as it increased spore germination. Furthermore, confocal and scanning electron microscopy (SEM) analyses showed a 27% increase in the spore size of S. indica in the presence of Z. sp. ISTPL4. In a liquid chromatography with tandem mass spectrometry (LC-MS/MS) analysis increased production of alanine and glutamic acid was observed in their sequential co-culture as compared with individual cultures. Sequential inoculation of S. indica and Z. sp. ISTPL4 significantly increased the biochemical and physical characteristics of rice as compared with their individual inoculum. Biochemical parameters such as chlorophyll content, total soluble sugar, and flavonoid content in the rice increased by up to 57%, 47%, and 39%, respectively, in the presence of the combined inoculum of S. indica and Z. sp. ISTPL4. This will be the first study, to the best of our knowledge, which shows the fungus and actinobacterium interaction and their synergistic roles in the growth promotion of rice. Furthermore, this novel combination can also be used to boost the growth of other crops to increase the agricultural yield.